THEORETICAL ANALYSIS OF DIFFERENTIATED EDUCATIONAL METHODS - Erkaboeva Nigora Shermatova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes a theoretical analysis of differentiated educational methods, in which modern educational methods, technologies and methods are scientifically covered.